2016
DOI: 10.1074/jbc.m115.696815
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the RcsB Response Regulator with Auxiliary Transcription Regulators in Escherichia coli

Abstract: The Rcs phosphorelay is a two-component signal transduction system that is induced by cell envelope stress. RcsB, the response regulator of this signaling system, is a pleiotropic transcription regulator, which is involved in the control of various stress responses, cell division, motility, and biofilm formation. RcsB regulates transcription either as a homodimer or together with auxiliary regulators, such as RcsA, BglJ, and GadE in Escherichia coli. In this study, we show that RcsB in addition forms heterodim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 62 publications
2
52
0
2
Order By: Relevance
“…Heterodimers between RR proteins have now been discovered in multiple instances (52)(53)(54)(55), suggesting that heterodimer formation may be a fundamental mechanism contributing to the concerted regulation of overlapping regulons in M. tuberculosis. We recently elucidated heterodimeric interactions between M. tuberculosis DevR and NarL RRs for co-regulation of gene expression during aerobic nitrate metabolism (22).…”
Section: Phop-devr Interaction Governs Expression Of Devr-devs Tcsmentioning
confidence: 99%
“…Heterodimers between RR proteins have now been discovered in multiple instances (52)(53)(54)(55), suggesting that heterodimer formation may be a fundamental mechanism contributing to the concerted regulation of overlapping regulons in M. tuberculosis. We recently elucidated heterodimeric interactions between M. tuberculosis DevR and NarL RRs for co-regulation of gene expression during aerobic nitrate metabolism (22).…”
Section: Phop-devr Interaction Governs Expression Of Devr-devs Tcsmentioning
confidence: 99%
“…The initiation of the Rcs signaling system leads to the phosphorylation of RcsB, enabling it to dimerize and function as a transcriptional regulator (28). Phosphorylated RcsB can also form a heterodimer with the auxiliary protein RcsA (29); the RcsB-RcsB and RcsA-RcsB complexes control the expression of a number of genes involved in acid resistance, as well as the colanic acid and curli synthesis operons, osmotically inducible peroxidase gene osmC, and the small regulatory RNA rprA (30)(31)(32). We found that activation of the Rcs pathway has little or no effect on Δcls cells growing planktonically.…”
mentioning
confidence: 99%
“…Regulation of flhD requires heterodimer formation of RcsB with the auxiliary protein RcsA, followed by binding to the conserved RcsAB box on the flhD promoter (40). Heterodimer formation can occur with a range of transcriptional regulators (41)(42)(43), often in a way that is unaffected by the phosphorylation state of RcsB (43,44) and instead favored at high concentrations of the protein (45). Altogether, the RcsCDB system has a myriad of functions in E. coli and other members of the family Enterobacteriaceae (9,(46)(47)(48)(49).…”
mentioning
confidence: 99%